Niobium doped Bi4Ti3O12 ceramics obtained by the polymeric precursor method - Simoes, A. Z.; Aguiar, E. C.; Ries, A.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2007)
Pure and niobium doped bismuth titanate ceramics (Bi4Ti3-xNbxO12 (BTN)), with x ranging from 0 to 0.4 were prepared by the polymeric precursor method. X-ray diffraction showed no secondary phases. Increasing niobium content leads to more resistive ceramics. The shape and size of the grains are strongly influenced by the niobiurn added to the system. The dielectric constant is not influenced by the niobium addition while hysteresis loops are significantly narrowed. (c) 2006 Elsevier B.V All rights reserved.
Keywords: ceramics; powder technology; sintering